The Economics of exchange rates : selected studies - Frenkel, Jacob A.; Johnson, Harry G. (Reading, Mass. : Addison-Wesley Pub. Co., 1978)
This book contains a series of studies dealing with the modern approach to the analysis of exchange rate determination as well as with the various characteristics of the foreign exchange market.
Includes bibliographies and index.
usc 10/04/18
Loans
Keywords: Foreign exchange rates